Gazetteer of Dehradun - "Walton, H. G." (Dehradun, 1996)
A general description of the Dehra Dun district. This project, if entertained, was never carried out, and the old Gazetteer contains very little of value for the purposes of his task. There is much useful information in Mr. G. R. C. Williams$1 (BMemoir of the Dun published in 1876 and author have fully drawn upon it but its interest is now chiefly historical, such has been the extraordinary progress of the district in the last 25 or 30 years. s
Keywords: Gazetteers- Dehradun